ACTIVITY OF VETERINARY DOCTORS IN FERGANA OBLAST (LATE XIX - EARLY XX CC.) (World Bulletin of Social Sciences, 2024)
This article describes the veterinary work of the Fergana region in the late XIX - early XX century. In general, at the end of XIX - beginning of XX century in Turkestan such cattle diseases as cholera, anthrax, emkar, common zotillas increased from year to year, and this situation hindered the development of cattle breeding in the country.